Governance, Experience, and Cultural Factors in the Adoption of IFRS for SMEs: Cross-Country Evidence from 88 Nations - Roekhudin, Roekhudin; Iqbal, Syaiful (International Review of Management and Marketing, 2026)
This study examines the determinants of adoption of the International Financial Reporting Standards for Small and Medium-Sized Entities (IFRS for SMEs) using cross-country evidence. Despite the growing importance of SMEs in global economies, empirical research on the adoption of IFRS for SMEs remains limited compared to studies on full IFRS. Drawing on data from 88 countries that have adopted IFRS for SMEs, this study investigates whether governance quality, prior experience with full IFRS, and cultural factors influence adoption decisions. Secondary data were obtained from the IFRS Foundation and the World Bank and analyzed using regression techniques. The findings indicate that governance-related factors do not constitute significant barriers to the adoption of IFRS for SMEs. Furthermore, experience with full IFRS and language-related cultural factors are not found to be significant determinants of adoption. These results suggest that IFRS for SMEs represents a flexible and broadly applicable reporting framework that can be implemented across diverse institutional environments. The study contributes to the international accounting literature by providing large-sample empirical evidence on IFRS for SMEs adoption and offers policy-relevant insights for regulators and standard setters seeking to promote harmonized financial reporting for SMEs.